2017
DOI: 10.1097/mcg.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Angioectasia

Abstract: These data help improve our knowledge of AEs regarding risk factors for rebleeding, and utilizes a novel small bowel transit time-based quartile localization method that may simplify future research and comparisons of anatomic distribution and behavior of small bowel AEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
10
1
1
Order By: Relevance
“…In this study, angioectasia was observed in the upper and middle portions, but not in the lower portion of the small bowel. Kaufman et al used a transit time-based quartile method to evaluate 158 patients with angioectasia who underwent CE and found that most lesions (67.1%) were in the first quartile [ 21 ]. Igawa et al reported that while there were no differences regarding the location of type 1a angioectasia among patients with occult gastrointestinal bleeding, type 1b angioectasia was relatively less frequent in the lower portion compared with that in the upper and middle portions of the small bowel [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, angioectasia was observed in the upper and middle portions, but not in the lower portion of the small bowel. Kaufman et al used a transit time-based quartile method to evaluate 158 patients with angioectasia who underwent CE and found that most lesions (67.1%) were in the first quartile [ 21 ]. Igawa et al reported that while there were no differences regarding the location of type 1a angioectasia among patients with occult gastrointestinal bleeding, type 1b angioectasia was relatively less frequent in the lower portion compared with that in the upper and middle portions of the small bowel [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although VCE has been recommended as the first-line investigation for SB bleeding, DAE still has an advantage over VCE for the histopathological confirmation of SB lesions and endoscopic hemostasis[ 2 , 3 ]. With regard to the source of SB bleeding, vascular lesions are the most common stigmata of hemorrhage, and DAE endotherapy has been considered as an efficient and safe treatment strategy[ 9 - 12 ]. Additionally, the rebleeding rate of SB vascular lesions is not low, especially in the elderly among individuals with active bleeding (identified by endoscopy), a history of aortic stenosis, or those in whom the bleeding source was angioectasia; the management of rebleeding using repeated endotherapy has favorable outcomes[ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the source of SB bleeding, vascular lesions are the most common stigmata of hemorrhage, and DAE endotherapy has been considered as an efficient and safe treatment strategy[ 9 - 12 ]. Additionally, the rebleeding rate of SB vascular lesions is not low, especially in the elderly among individuals with active bleeding (identified by endoscopy), a history of aortic stenosis, or those in whom the bleeding source was angioectasia; the management of rebleeding using repeated endotherapy has favorable outcomes[ 9 , 10 ]. Among SB vascular lesions, arteriovenous malformation bleeding can be life-threatening; hence, prompt identification and timely intervention are very important[ 13 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, risk factors for rebleeding attributed to AE were summarized from six studies (primarily utilizing capsule endoscopy and small bowel enteroscopy) in which rebleeding was associated with cirrhosis, a bleeding locus in the distal small bowel, and multiple AE. Unfortunately, since the contribution of endoscopic treatment toward the achievement of hemostasis was not uniformly collected in these studies, no further data were available regarding the understanding of the contribution of endoscopic cauterization toward the reduction of rebleeding risk [17]. Further studies will be required to quantify the benefit of endoscopic therapies, in particular those delivered to small bowel AE, and reductions in rebleeding risk.…”
mentioning
confidence: 99%